131 iodine gamma dose determination in the thyroid gland using two geometrical shapes: a comparative study. (2nd April 2015) - Betka, A; Bentabet, A; Azbouche, A; Fenineche, N; Adjiri, A; Dib, A
Abstract: In order to study the internal gamma dose, we used a Monte Carlo code 'Penelope' simulation with two geometrical models (cylindrical and spherical). The deposited energy was determined via the loss of energy calculated from the quantum theory for inelastic collisions based on the first-order (plane-wave) Born approximation for charged particles with individual atoms and molecules. Our results show that the cylindrical geometry is more suitable for carrying out such a study. Moreover, we developed an analytical expression for the 131 iodine gamma dose (the energy deposited per photon absorbed dose). This latter could be considered as an important tool for evaluating the gamma dose without going through stochastic models.